Silent Progressive Glaucoma in Encephalofacial angiomatosis (Sturge-Weber Syndrome): A Vision-Preserving Trabeculectomy: Poster Presentation - Case Report - Resident - Gunardi, Triana Hardianti; Iskandar, Ferdy; Herdian, Felicia Sesi; Amanda, Lia; Priscilla, Florentina; Oktariana, Virna Dwi (Majalah Oftalmologi Indonesia, 2023)
Introduction : Encephalofacial angiomatosis, also known as Sturge-Weber Syndrome (SWS), is a rare, non- hereditary condition affecting multiple organs. Glaucoma occurs in almost 70% SWS children, more commonly when the port-wine stain involves the upper eyelid skin. Secondary glaucoma was present due to elevated venous pressure. Case Illustration : An 8-year-old boy with typical port-wine stain involving eyelid, came with recurrent painful right eye (RE) and headache in the past 3 months. He was diagnosed with SWS at 1 year and was on daily doses of carbamazepine and valproic acid for seizure control. His best visual acuity and intraocular pressure were 0.5/60 RE, 6/38 LE, 38 mmHg RE, 28 mmHg LE, respectively. Examination revealed Cup-disc-ratio (CDR) 0.9-1.0 RE and 0.5-0.6 LE. During the first three months, he showed favourable outcome with timolol and latanoprost (controlled IOP with target of <12 mmHg and markedly similar Cup-Disc Ratio). However, at 4th and 5th month visit, his IOP significantly increased despite of additional regiments, thus underwent trabeculectomy on both eyes for preserving his sight. After procedure, his IOP remained stable <12mmHg with maintained bleb, deep anterior chamber, also attached posterior segment. Discussion : Treatments of secondary glaucoma of SWS typically involved surgery with significantly lower success rate compared to Primary Congenital Glaucoma. Trabeculectomy or tube shunt surgery should be performed with caution due to risks of choroidal effusion and hemorrhages. Conclusion : Secondary glaucoma in children with SWS is common and challenging. Trabeculectomy should be pursued when the benefit outweighs the risks, even with a slim chance, to preserve the vision.